Prognostic value of diffusion-weighted MRI for post-cardiac arrest coma - Hirsch, Karen G; Fischbein, Nancy; Mlynash, Michael; Kemp, Stephanie; Bammer, Roland; Eyngorn, Irina; Tong, Julia; Moseley, Michael; Venkatasubramanian, Chitra; Caulfield, Anna Finley; Albers, Gregory (Neurology, 2020)
To validate quantitative diffusion-weighted imaging (DWI) MRI thresholds that correlate with poor outcome in comatose cardiac arrest survivors, we conducted a clinician-blinded study and prospectively obtained MRIs from comatose patients after cardiac arrest. Consecutive comatose post-cardiac arrest adult patients were prospectively enrolled. MRIs obtained within 7 days after arrest were evaluated. The clinical team was blinded to the DWI MRI results and followed a prescribed prognostication algorithm. Apparent diffusion coefficient (ADC) values and thresholds differentiating good and poor outcome were analyzed. Poor outcome was defined as a Glasgow Outcome Scale score of ≤2 at 6 months after arrest. Ninety-seven patients were included, and 75 patients (77%) had MRIs. In 51 patients with MRI completed by postarrest day 7, the prespecified threshold of >10% of brain tissue with an ADC <650 ×10 mm /s was highly predictive for poor outcome with a sensitivity of 0.63 (95% confidence interval [CI] 0.42-0.80), a specificity of 0.96 (95% CI 0.77-0.998), and a positive predictive value (PPV) of 0.94 (95% CI 0.71-0.997). The mean whole-brain ADC was higher among patients with good outcomes. Receiver operating characteristic curve analysis showed that ADC <650 ×10 mm /s had an area under the curve of 0.79 (95% CI 0.65-0.93, < 0.001). Quantitative DWI MRI data improved prognostication of both good and poor outcomes. This prospective, clinician-blinded study validates previous research showing that an ADC <650 ×10 mm /s in >10% of brain tissue in an MRI obtained by postarrest day 7 is highly specific for poor outcome in comatose patients after cardiac arrest.